Dietary supplementation with soluble corn fiber improved fecal score, microbiota, and SCFAs in dogs - Liang, Donghui; Zhao, Shuai; Yin, Guoan (Frontiers in Veterinary Science, 2025)
IntroductionSoluble corn fiber, a safe dietary fiber with prebiotic properties, has been put to several applications in human daily life. However, studies on its use in pet food are scarce. This study was conducted to investigate the effects of SCF on microbial diversity, SCFAs and fecal quality in canines.MethodsTwenty adult dogs were divided into four groups, including the control group (CON) and three groups fed diet supplemented with 0.1% (SCF1), 0.5% (SCF2), or 1% (SCF3) SCF for 21 days.ResultsFecal scores of the group fed 1% SCF were the closest to the ideal state. α-diversity analysis showed the Chao1 index in the SCF2 and SCF3 groups was significantly higher (p < 0.05) than in the CON group, indicating an increase in colony abundance. β-diversity analysis showed no significant structural difference among groups (p > 0.05). Microbial diversity analysis showed the addition of SCF to the diets increased the relative abundance of Bacteroidota and Blautia and decreased the relative abundance of Firmicutes, [Ruminococcus]_gnavus_group, and Prevotellaceae_Ga6A1_group; 1% SCF the relative abundance of Prevotella and Blautia (p < 0.05), and the content of acetic acid, valeric acid, and isobutyric acid (p < 0.05) and significantly decreased the content of butyric acid (p < 0.05).ConclusionDietary supplementation with SCF improves the fecal condition, modulates microbiota composition, enhances the levels of acetic acid, valeric acid, and isobutyric acid, and decreases the level of butyric acid in dogs, with optimal effects observed for 1% supplementation.